Pituitary Tumors: What Are They and How Are They Treated? - Wijaya Juwarna; Donny Donny; Marsal Rifandi; Diki Fauzi Sultoni; Santa Riviera Filia; Yohana Maria Paulina Marpaung; Gabriel Samlana Pinem; El Yoenay Ivanema Maduwu (SEAN Institute, 2026)
The pituitary gland (hypophysis) is a very small, pea-sized gland located inside the skull, specifically beneath the brain and above the back of the nasal cavity. However, if the gland grows beyond its normal size (tumor), it can compress and damage the brain and nerves, leading to hormonal disorders and even blindness. Most pituitary tumors are benign. Their symptoms vary depending on the type of tumor and the areas around the pituitary gland that are affected. Many patients present with visual disturbances or even blindness. Although benign, progressive growth can cause symptoms that significantly affect the patient's quality of life. Management of pituitary tumors may include radiotherapy, medication, and surgery. Surgery is the primary treatment for pituitary tumors. Currently, the Endoscopic Skull Base Surgery (ESBS), Transsphenoidal Approach (TSA), has become one of the techniques that offers advantages such as shorter stays in the ICU and hospital ward, reduced risks and minimal bleeding during surgery, faster recovery, and no facial incisions (better cosmetic outcome).